-(3x-3)-(2x-6)+3=-5(x-1)-(3x+2)+3

Simple and best practice solution for -(3x-3)-(2x-6)+3=-5(x-1)-(3x+2)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3x-3)-(2x-6)+3=-5(x-1)-(3x+2)+3 equation:


Simplifying
-1(3x + -3) + -1(2x + -6) + 3 = -5(x + -1) + -1(3x + 2) + 3

Reorder the terms:
-1(-3 + 3x) + -1(2x + -6) + 3 = -5(x + -1) + -1(3x + 2) + 3
(-3 * -1 + 3x * -1) + -1(2x + -6) + 3 = -5(x + -1) + -1(3x + 2) + 3
(3 + -3x) + -1(2x + -6) + 3 = -5(x + -1) + -1(3x + 2) + 3

Reorder the terms:
3 + -3x + -1(-6 + 2x) + 3 = -5(x + -1) + -1(3x + 2) + 3
3 + -3x + (-6 * -1 + 2x * -1) + 3 = -5(x + -1) + -1(3x + 2) + 3
3 + -3x + (6 + -2x) + 3 = -5(x + -1) + -1(3x + 2) + 3

Reorder the terms:
3 + 6 + 3 + -3x + -2x = -5(x + -1) + -1(3x + 2) + 3

Combine like terms: 3 + 6 = 9
9 + 3 + -3x + -2x = -5(x + -1) + -1(3x + 2) + 3

Combine like terms: 9 + 3 = 12
12 + -3x + -2x = -5(x + -1) + -1(3x + 2) + 3

Combine like terms: -3x + -2x = -5x
12 + -5x = -5(x + -1) + -1(3x + 2) + 3

Reorder the terms:
12 + -5x = -5(-1 + x) + -1(3x + 2) + 3
12 + -5x = (-1 * -5 + x * -5) + -1(3x + 2) + 3
12 + -5x = (5 + -5x) + -1(3x + 2) + 3

Reorder the terms:
12 + -5x = 5 + -5x + -1(2 + 3x) + 3
12 + -5x = 5 + -5x + (2 * -1 + 3x * -1) + 3
12 + -5x = 5 + -5x + (-2 + -3x) + 3

Reorder the terms:
12 + -5x = 5 + -2 + 3 + -5x + -3x

Combine like terms: 5 + -2 = 3
12 + -5x = 3 + 3 + -5x + -3x

Combine like terms: 3 + 3 = 6
12 + -5x = 6 + -5x + -3x

Combine like terms: -5x + -3x = -8x
12 + -5x = 6 + -8x

Solving
12 + -5x = 6 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
12 + -5x + 8x = 6 + -8x + 8x

Combine like terms: -5x + 8x = 3x
12 + 3x = 6 + -8x + 8x

Combine like terms: -8x + 8x = 0
12 + 3x = 6 + 0
12 + 3x = 6

Add '-12' to each side of the equation.
12 + -12 + 3x = 6 + -12

Combine like terms: 12 + -12 = 0
0 + 3x = 6 + -12
3x = 6 + -12

Combine like terms: 6 + -12 = -6
3x = -6

Divide each side by '3'.
x = -2

Simplifying
x = -2

See similar equations:

| -87-9x=4x+186 | | (27)^(5/3) | | X^3+6=0 | | y=7/8(2)+5y | | 5.4-3.8+(-22)= | | 1/7(x+5)=7 | | X+1=5x+25 | | 6x+7=4-3(x+2) | | -8=-5(w+5) | | 2(x-6)+3=-3(4-x) | | 6x-12y=72 | | y=-7+5y | | 6x-16-3x=5x-9 | | 2-b+7b-2= | | 8.9y-7.35=12.4y | | 3-6x=-2x-37 | | 6+.10x=0.15x+8 | | -7x+7(-3x+18)=-14 | | 15h-11h=20 | | 1.25n=4 | | -5/6+x=11/6 | | -5=(x+9) | | 12x+14+10v=80 | | 36/x-8=6/7 | | 5x-9=-3x-25 | | x/5-13=22 | | y=7/8(0)+5y | | 6x+2(6x-3)=-144 | | 2x-2x/7=x/2+17/2 | | 16x+1=-14 | | 2(x+10)=x-7 | | -5(w+5)= |

Equations solver categories